A triazine-based covalent organic framework/palladium hybrid for one-pot silicon-based cross-coupling of silanes and aryl iodides1. Issue 51 (5th June 2015) - Lin, Sha; Hou, Yuxia; Deng, Xiao; Wang, Haoliang; Sun, Shuzhuang; Zhang, Xiaomei
<x xml:space="preserve">Abstract</x> A palladium/COF hybrid material could efficiently catalyze the silicon-based one-pot cross-coupling reaction of silanes and aryl iodides with excellent selectivity.